Labor Market Experience in a Pseudo-Home Country: Turkish Immigrants in Northern Cyprus - Besim, Mustafa; Ekici, Tufan; Guven-Lisaniler, Fatma (Routledge Journals, Taylor & Francis Ltd, 2015)
In this study we analyze the labor market experiences of Turkish immigrants in Northern Cyprus. Northern Cyprus presents a unique example for Turkish migrants, as many traditional obstacles (language barrier, cultural and ethnic differences and non-transferability of human capital) for immigrant laborers are not applicable since Turkish immigrants have ethnic and cultural similarities to native citizens and Turkey is considered the motherland of Northern Cyprus. Nonetheless, significant differences between Turkish immigrants and natives in regard to the labor market exist in Northern Cyprus. Using data from the period 2004-2011, we find that although occupational attainment of immigrants has improved in favor of high-skilled occupations, the average wage gap has not decreased significantly. The statistical estimations reveal that Turkish immigrants earn, on average, 25 percent less than natives in the private sector. Furthermore, half of this gap cannot be explained by differences in individual characteristics and ethnic discrimination.
Keywords: Wage Differentials; Earnings; Migration; Workers; Americanization; Assimilation; Language; Returns